2014
DOI: 10.17784/mtprehabjournal.2014.12.188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microelectrólisis Percutaneous (MEP ®) on pain and functionality in patients with calcaneal tendinopathy.

Abstract: Introduction: The Achilles tendinopathy with tendon injuries are the third most common in the musculoskeletal system. New therapies have been proposed for the treatment of tendinopathy as Percutaneous Microelectrólisis (MEP ®). Objectives: The aim of this study was to evaluate the effects of MEP ® on tendinopathy of Achilles. Method: This was a controlled clinical trial, randomized study. The sample comprised 20 patients with Achilles tendinopathy. The volunteers were randomly divided into two groups, control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…MEP is a new therapeutic pro posal that uses dC percutaneously through acupuncture needles, and its foundation is also based on the generation of a controlled local inflammatory process accompanied by analgesic effects resulting from the cathode polar effect. MEP is more comfortable than other percutaneous electrical inter ventions because it uses a microcurrent [8][9][10][11]31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MEP is a new therapeutic pro posal that uses dC percutaneously through acupuncture needles, and its foundation is also based on the generation of a controlled local inflammatory process accompanied by analgesic effects resulting from the cathode polar effect. MEP is more comfortable than other percutaneous electrical inter ventions because it uses a microcurrent [8][9][10][11]31].…”
Section: Discussionmentioning
confidence: 99%
“…it is also reported that the caustic reaction would maintain the analgesic effect by de stroying local free nerve endings that process nociceptive in formation. Furthermore, the mechanical stimulus of the needle generates a micro tissue break, accompanied by physiologi cal effects of electrical stimulus [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next question, 293 professionals and a total of 22 participants ignored the answer. A question with multiple options is presented closed with a single selection and the results are the following: "Unsatisfied": 0% (0); "Little satisfied": 1.71% (5); "Neutral": 5.46% (16); "Satisfied": 51.87% (152) and "Very satisfied": 40.96% (120). Figure 3 shows the nominal representation of the results obtained.…”
Section: Figure 1 Complications With Mep® Sportmentioning
confidence: 99%
“…This generates NaOH that produces a liquefaction of adjacent tissues, triggering an acute controlled inflammatory process. On the other hand, H 2 is released, which inhibits the free radicals present in tendinopathies and muscle injuries [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%